Food- and feed-based nutrient flows in two West African cities - Karg, H.; Akoto-Danso, Edmund K.; Drechsel, Pay; Abubakari, A.H.; Buerkert, Andreas (Springer, 2019)
Recent studies have examined the urban metabolism of cities using urban consumption as a proxy for food inflows but very few studies have aimed at quantifying the role of cities as trade hubs and nutrient sinks of their hinterlands. We therefore examined the linkages between food and animal feed supply, their places of production and nutrient flows through the urban system in the two West African cities of Tamale (Ghana) and Ouagadougou (Burkina Faso). Using primary data on food and feed flows, and secondary data to assess the transformation of these flows into nutrient terms, we show that, besides urban consumption, the function of the two study sites as trade hubs significantly determines nutrient flows. In Tamale, > 50% of the nutrient inflows was neither consumed nor was lost in situ but left that city again for other destinations. At least 30% of the incoming cereals was stored in the city for later consumption or export. Ouagadougou relied more on imported goods with 40% of N imported from foreign countries compared to Tamale where only 10% of the N was imported, thus contributing to heavier nutrient extraction in remote production areas.